The Development of Nutrition Demand Enquiry Model for Preschool-Aged Children Based on Health Promotion Model - Eka Mishbahatul Mar'ah Has; Florentina Sustini; Ni Ketut Alit Armini (Universitas Airlangga, 2012)
Introduction: Preschool-aged children are not able to manage their nutrition independently. They need help, especially from their mother. Mother's behavior has effect on preschool's nutritional status. The aim of this study was to develop nutrition demand enquiry model for preschool-aged children based on Health Promotion Model.Method: Design used in this research was an observational analytic with cross sectional approach that was conducted in Karangturi Village, Gresik, East Java. The population was mothers of preschool aged children listed on Integrated Health Post for Underﬁves (Posyandu Balita) along April–May 2012. Simple random sampling was used to take the sample. Sample size was 90 respondents. The independent variables were personal factors (age, motivation, and ethnicity), perceived beneﬁt, perceived barrier, perceived self-efﬁcacy, and commitment. The dependent variable was mother's behavior on nutrition of preschool children. Data were collected using questionnaire and food recall 24 hour. Data were analyzed using PLS (Partial Least Square) Regression.Result: The result showed that 1) personal factors had correlation with perceived beneﬁt, perceived barrier, and perceived self-efﬁcacy; 2) perceived beneﬁt and perceived barrier had correlation with commitment; 3) commitment had no correlation with mother's behavior on nutrition. Perceived beneﬁt and perceived barrier had direct correlation with mother's behavior on nutrition. Discussion: It can be concluded that mother's perceived beneﬁt and perceived barrier was correlated with mother's behavior on nutrition. Nurses are key health care professionals responsible for increasing health education activities about how to manage nutrition of preschool age children. So, mother should have good behavior on preschool age children's nutrition.